2021
DOI: 10.3390/ijms222112020
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of the Biochemical Mechanisms and Epigenetic Modifications in HIV- and Antiretroviral-Induced Metabolic Syndrome

Abstract: Metabolic syndrome (MetS) is a non-communicable disease characterised by a cluster of metabolic irregularities. Alarmingly, the prevalence of MetS in people living with Human Immunodeficiency Virus (HIV) and antiretroviral (ARV) usage is increasing rapidly. This study aimed to look at biochemical mechanisms and epigenetic modifications associated with HIV, ARVs, and MetS. More specifically, emphasis was placed on mitochondrial dysfunction, insulin resistance, inflammation, lipodystrophy, and dyslipidaemia. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 97 publications
0
31
0
Order By: Relevance
“…Recent reports have linked some HIV-related features to MetS. These characteristic features include escalated cases of cardiovascular diseases, type 2 diabetes mellitus, dyslipidemia, immunodeficiency, high viral load, and atherosclerosis [ 7 ]. Recently, studies have suggested that HAART, in addition to the above-mentioned HIV-related features, actively induces MetS in persons with HIV [ 7 , 39 , 40 , 41 ].…”
Section: The Roles Of Hiv and Haart In Metsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent reports have linked some HIV-related features to MetS. These characteristic features include escalated cases of cardiovascular diseases, type 2 diabetes mellitus, dyslipidemia, immunodeficiency, high viral load, and atherosclerosis [ 7 ]. Recently, studies have suggested that HAART, in addition to the above-mentioned HIV-related features, actively induces MetS in persons with HIV [ 7 , 39 , 40 , 41 ].…”
Section: The Roles Of Hiv and Haart In Metsmentioning
confidence: 99%
“…These characteristic features include escalated cases of cardiovascular diseases, type 2 diabetes mellitus, dyslipidemia, immunodeficiency, high viral load, and atherosclerosis [ 7 ]. Recently, studies have suggested that HAART, in addition to the above-mentioned HIV-related features, actively induces MetS in persons with HIV [ 7 , 39 , 40 , 41 ]. Earlier studies by Palios et al (2011) on arterial stiffness, displayed by pulse wave velocity (PWV), and markers of MetS, reported that persons with HIV exhibited an increased degree of PWV when compared with the healthy controls.…”
Section: The Roles Of Hiv and Haart In Metsmentioning
confidence: 99%
See 1 more Smart Citation
“…Small-molecule inhibitors targeting PI3 kinase VPS34 or fatty acid metabolism have been shown to inhibit SARS-CoV-2 activity [77] . HIV infection in adulthood is more likely to cause metabolic syndrome, which includes excess abdominal fat, abnormal blood sugar and lipid levels, and high blood pressure, as well as an increased risk of diabetes, heart disease, and stroke [78] , [79] . All of these are attributable to HIV itself, inflammation, and side effects of antiretroviral therapy [79] .…”
Section: Roles Of Il-6-mediated Immunometabolic Reprogramming In Vira...mentioning
confidence: 99%
“…HIV infection in adulthood is more likely to cause metabolic syndrome, which includes excess abdominal fat, abnormal blood sugar and lipid levels, and high blood pressure, as well as an increased risk of diabetes, heart disease, and stroke [78] , [79] . All of these are attributable to HIV itself, inflammation, and side effects of antiretroviral therapy [79] . AIDS-related inflammation and immune activation also occur throughout the infection and treatment process, which is related to the persistence of HIV, translocation of intestinal flora, reduction of regulatory T cells, and combination or secondary infection with other viruses [80] , [81] .…”
Section: Roles Of Il-6-mediated Immunometabolic Reprogramming In Vira...mentioning
confidence: 99%